CCSP (ISC)2 certified cloud security professional official study guide - O'Hara, Brian T.; Malisow, Ben (Sybex, 2017)
The only official study guide for the new CCSP exam CCSP (ISC)2 Certified Cloud Security Professional Official Study Guide is your ultimate resource for the CCSP exam. As the only official study guide reviewed and endorsed by (ISC)2, this guide helps you prepare faster and smarter with the Sybex study tools that include pre-test assessments that show you what you know, and areas you need further review. Objective maps, exercises, and chapter review questions help you gauge your progress along the way, and the Sybex interactive online learning environment includes access to a PDF glossary, hundreds of flashcards, and two complete practice exams. Covering all CCSP domains, this book walks you through Architectural Concepts and Design Requirements, Cloud Data Security, Cloud Platform and Infrastructure Security, Cloud Application Security, Operations, and Legal and Compliance with real-world scenarios to help you apply your skills along the way. The CCSP is the latest credential from (ISC)2 and the Cloud Security Alliance, designed to show employers that you have what it takes to keep their organization safe in the cloud. Learn the skills you need to be confident on exam day and beyond. -Review 100% of all CCSP exam objectives -Practice applying essential concepts and skills -Access the industry-leading online study tool set -Test your knowledge with bonus practice exams and more As organizations become increasingly reliant on cloud-based IT, the threat to data security looms larger. Employers are seeking qualified professionals with a proven cloud security skillset, and the CCSP credential brings your resume to the top of the pile. CCSP (ISC)2 Certified Cloud Security Professional Official Study Guide gives you the tools and information you need to earn that certification, and apply your skills in a real-world setting.